1982
DOI: 10.1172/jci110475
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostaglandin E2 in mediating the effects of pH on the hydroosmotic response to vasopressin in the toad urinary bladder.

Abstract: A B S T R A C T Acidosis inhibits the hydroosmotic response to vasopressin. Since prostaglandins are known to modulate vasopressin-stimulated water flow we investigated the role of endogenous prostaglandin E2(PGE2) production in the pH-dependent response of the toad urinary bladder to vasopressin. Graded acidification of the serosal media resulted in a progressive decline in vasopressin-stimulated water flow from 26.6±0.5 mg/min at pH 8.4 to 1.7±0.6 at pH 6.9. In these bladders basal PGE2 synthesis increased f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1982
1982
2001
2001

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…Prostaglandins inhibit the ADH-induced increase in water permeability (29,35) by acting at pre-and post-cAMP steps (35); their synthesis can be activated by Ca2+ (29). Through the use of indomethacin, we indirectly tested the possibility that the extracellular Ca2+-dependent inhibitions may be mediated by endogenous prostaglandins.…”
Section: Effect Of Indomethacin On the Ca2+-mediated Inhibition Ofpumentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandins inhibit the ADH-induced increase in water permeability (29,35) by acting at pre-and post-cAMP steps (35); their synthesis can be activated by Ca2+ (29). Through the use of indomethacin, we indirectly tested the possibility that the extracellular Ca2+-dependent inhibitions may be mediated by endogenous prostaglandins.…”
Section: Effect Of Indomethacin On the Ca2+-mediated Inhibition Ofpumentioning
confidence: 99%
“…The indomethacin concentration (lO-1 M) and time of incubation (120 min) employed completely abolishes prostaglandin E2 production (29). Prostaglandin E2 inhibits ADH action on both water permeation and Pu, though it is much more effective on the former than on the latter (2).…”
Section: Effect Of Indomethacin On the Ca2+-mediated Inhibition Ofpumentioning
confidence: 99%
“…Indeed, a number of previously published studies suggested that acid-base changes did modify PGs synthesis (5)(6)(7)(8)(9)(10).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that acidification of the serosal medium of the toad bladder inhibits the action of ADH (5)(6)(7)(8)(9). Recently, Forrest et al (9) confirmed these results and demonstrated that acidification of the medium is also associated with increased prostaglandin E2 (PGE2) production. The addition of meclofenamate or indomethacin, inhibitors of PG production, to acidified bladders restored the effect of ADH.…”
mentioning
confidence: 99%
“…In nonosseus cells, metabolic acidosis increases the levels of prostaglandins (1,34,35,41). In both toad bladder (34,35) and rat kidney (41), PGE 2 levels have been shown to increase in response to metabolic acidosis.…”
mentioning
confidence: 99%